Techno-stress and productivity: Survey evidence from the aviation industry. (January 2016) - Alam, Muhammad Aftab
Abstract : Technological progress in aviation sector is a source of increasing productivity, yet it is also a cause of stress. This study aimed to elucidate the linkage between techno-stress and crew productivity and examine the interaction effect of role-overload and equity-sensitivity in this relationship. The study explored three factors of techno-stress i.e. techno-complexity, techno-uncertainty and techno-overload, and found that their negative relationship with crew productivity got stronger when the crew was more role-overloaded and when the crew was more equity-sensitive. Respondents (N = 203) randomly chosen from aviation sector in Pakistan participated in the study. Together, the findings suggested role-equity analogous to fulcrum that can leverage crew productivity in aviation industry. Highlights: Techno-stress and crew productivity are inversely related in the aviation sector. The relationship gets stronger when the crew is either 'role-overloaded' or 'equity-sensitive'. It gets critical when the already role-overloaded crew also becomes equity-sensitive. Together, role-equity (analogous to 'fulcrum') has stern implications for crew productivity owing to rising techno-stress.